Asuhan Keperawatan Bersihan Jalan Napas Tidak Efektif (PPOK) dengan Latihan Batuk Efektif di RSUD dr. R. Soedarsono - Alif Alwi; Erik Kusuma; Syaifuddin Kurnianto; Dwining Handayani (Inovasi Kesehatan Global, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is defined as a non-communicable disease related to the respiratory system, where airway spasm occurs which is interpreted through shortness of breath, decreased oxygen saturation, and increased sputum production. This sputum production is caused by exposure to harmful substances that can inhibit mucociliary clearance, goblet cell proliferation occurs which causes hyperplasia and hypertrophy resulting in the growth and enlargement of mucous glands which results in increased sputum production and causes ineffective airway clearance nursing problems. The purpose of this study was to describe nursing care for ineffective airway clearance (COPD) with effective cough training at RSUD dr. R. Soedarsono. Methods: This research used a case study design. The research participants were COPD patients with ineffective airway clearance nursing problems who were given interventions in the form of effective cough training in Interna Room 2 at RSUD dr. R. Soedarsono. Data collection was done through interviews, observation, physical examination, and documentation. Results: Ineffective airway clearance is resolved as shown by the patient saying the cough has decreased and is not tight, able to remove phlegm, additional breath sounds decrease, sputum production decreases and breathing frequency is 20x/minute. Conclusion: Effective cough training is proven to be effective in improving airway clearance in COPD patients, so it can be one of the non-pharmacological interventions to overcome this problem.